"Speak with Girls, Not for Them": Supporting Girls' Action Against Rape Culture. Issue 1 (1st March 2021) - Bernier, Alexe; Winstanley, Sarah
Abstract: Reflecting on our work with girls, we discuss what we have learned about how they experience rape culture and engage in activism to confront it. We explore how rape culture manifests in the lives of adolescent girls who are between 10 and 15 years of age in Calgary, Canada. We then demonstrate how groups of girls have moved from awareness to collective action meant to challenge rape culture and consider the impact that this action has had on them. Our aim is to show how popular education and feminist methodologies are effective in supporting girls' activism on issues like rape culture so that others working in community with girls may gain new tools that might aid their work.